Prisma Espaço Geek: um espaço público disruptivo de aprendizagem criativa para a formação do leitor contemporâneo - D'Arienzo, Maria Augusta (2023)
The formation of readers is an emerging theme in debates in the field of education and is even more relevant when it is reflected in the context of the State and National Capital of Literature, a title that Passo Fundo/RS has been granted by law. This thesis, which has Prisma Espaço Geek as its object of study, introduces a new moment in the formation of contemporary readers. In this sense, this study seeks to answer the following research problem: what are the challenges and opportunities of a disruptive public space for developing contemporary readers in the digital culture? To this end, the main goal is to present the potential and challenges of creating a disruptive public space for creative learning to educate contemporary readers, specifically Prisma Espaço Geek. In order to answer the proposed question and achieve the objectives, the research was qualitative, applicable and a case study, and used the descriptive research method to explain the reader development proposal implemented through the activities of Prisma Espaço Geek. To this end, Chartier's (1998; 2016), Zilberman's (2001; 2016), Santaella's (2004; 2013; 2016; 2021), Dewey's (1979), Bruner's (1997; 2000; 2013), Papert's (1994), Resnick's (2020) and Christensen's (2012) contributions to reading, developing contemporary readers, creative learning and disruptive education were used as theoretical contributions to the research. The use of a hybridization of references is justified by the complex and multifaceted nature of the object of study. The application and case study took into account the period from the creation of the "PRISMA: Estação Cultural da Gare" project to its implementation and embodiment as Prisma Espaço Geek, from 2015 to 2023. The study revealed that the narratives that permeate digital culture and are disseminated by geek culture have the potential to meet the demands of the new ways of reading and writing in contemporary times. At the same time, it showed that the use of disruptive education provides learning conditions to mobilize the skills and competences needed to train readers in the context of digital culture. It was concluded that the creation of a disruptive public space for creative learning in order to develop contemporary readers helps to show that the transgression of structural paradigms and mentalities encourages the development of creative thinking using different languages, media and innovative approaches. It was also concluded, in this direction, that such development makes it possible to prepare subjects for experiences in a world in constant transformation and that the initial and continuing formation of the subjects who develop this proposal presents itself as a challenge to its implementation